Personalized learning through 1:1 technology initiatives: implications for teachers and teaching in neoliberal times. Issue 3 (3rd July 2019) - Hallman, Heidi L.
Abstract: Situated within the broader context of neoliberalism, this article explores how personalized learning, as tied to 1:1 technology initiatives, prompts changes in teachers' classrooms and practices. The article draws upon a case study of one novice teacher as a way to view how personalized learning is undergirded by tenets of neoliberalism that ultimately change the relationship between teachers, students, and knowledge. While this article does not dispute the positive effects that personalized learning through technology has offered to many students, it explores facets of how such a change has reoriented the role of the teacher and repositioned knowledge as it relates to classrooms and students.